2012
DOI: 10.3109/0886022x.2012.712860
|View full text |Cite
|
Sign up to set email alerts
|

Volume Status in Patients on Peritoneal Dialysis: The Role of Apelin and Bio-Impedance Spectroscopy

Abstract: One of the main factors determining the survival of peritoneal dialysis (PD) patients is volume status. We aimed to investigate hydration status of PD patients by bio-impedance spectroscopy (BIS) and echocardiography and to study the relation of them with apelin, which has effects related with volume status like vasodilation, positive inotropism, and inhibition of ADH release and RAS antagonism. Chronic PD patients without active cardiac disease or clinically prominent hypervolemia were included. Besides the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This unexpected result may be due to limited number of patients. 28 In our study, it is detected that LVMI and serum apelin level in patient group was significantly higher than control group. As the patient group was divided into two groups as high and low apelin groups, LVMI is higher in high apelin group than low apelin group, but not statistically significant.…”
Section: Discussionmentioning
confidence: 65%
“…This unexpected result may be due to limited number of patients. 28 In our study, it is detected that LVMI and serum apelin level in patient group was significantly higher than control group. As the patient group was divided into two groups as high and low apelin groups, LVMI is higher in high apelin group than low apelin group, but not statistically significant.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, Karadag and Kazancioglu et al reported positive association between apelin and LDL in PD patients. 31,34 However, Malyszko et al found apelin was negatively correlated with TG, total and LDL cholesterol in HD patients. 38 The controversy between those studies might be due to dialysis modality as PD patients are more predisposed to metabolic disturbances, particularly to hyperglycemia and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 However we did not directly analyze body fluid composition by bio-impedance spectroscopy (BIA). Although all measurements were done in euvolemic state, hypervolemia was not actually ruled out because of hypertension and hypoalbuminemia, particularly in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, edemafree status does not always indicate the state of euvolemia [28]. This is because some pathologic alterations in dialysis patients, including vascular permeability and stiffness, cardiac dysfunctions, and use of vasodilator medications, may interfere with accurately interpreting volume status [29,30]. Second, a study has shown that the severity of pedal edema was not associated with more objective methods of assessing the volume status, including IVC diameter measurement or serum biomarkers [30].…”
Section: Discussionmentioning
confidence: 99%
“…In line with a previous study [28], we speculate that increments in OH are one of the main contributors to edema formation in PD patients. However, some pathologic alterations in dialysis patients, including vascular permeability and stiffness, cardiac dysfunctions, and use of vasodilator medications, may interfere with accurately interpreting volume status using edema assessment [29,30]. Moreover, the mechanism behind edema formation in dialysis is multifactorial, and some other contributors, like hypoalbuminemia, should be considered in evaluating edematous patients [28].…”
Section: Discussionmentioning
confidence: 99%